2018
DOI: 10.1175/jas-d-17-0375.1
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Tropical Atmosphere in Moisture Space

Abstract: Measurements from the Barbados Cloud Observatory are analyzed to identify the processes influencing the distribution of moist static energy and the large-scale organization of tropical convection. Five years of water vapor and cloud profiles from a Raman lidar and cloud radar are composed to construct the structure of the observed atmosphere in moisture space. The large-scale structure of the atmosphere is similar to that now familiar from idealized studies of convective self-aggregation, with shallow clouds p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 55 publications
(75 reference statements)
2
37
0
Order By: Relevance
“…While the nocturnal increase of latent heating (Figure h) linked to boundary layer rooted convection is likely critical to the diurnal change in ω in the lower‐midtroposphere (Ciesielski et al, ; Ruppert & Hohenegger, ), here we test the notion that SW ∗ directly drives the circulation change in the middle‐upper troposphere. This effect can be approximated from the weak temperature gradient approximation (Sobel et al, ) through ωSW=false[SWfalse]()sp1, where s is dry static energy, and [ ] ′ denotes a deviation from the daily mean (Ruppert & Hohenegger, ; Schulz & Stevens, ). ω SW is shown in Figure d for night and day.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the nocturnal increase of latent heating (Figure h) linked to boundary layer rooted convection is likely critical to the diurnal change in ω in the lower‐midtroposphere (Ciesielski et al, ; Ruppert & Hohenegger, ), here we test the notion that SW ∗ directly drives the circulation change in the middle‐upper troposphere. This effect can be approximated from the weak temperature gradient approximation (Sobel et al, ) through ωSW=false[SWfalse]()sp1, where s is dry static energy, and [ ] ′ denotes a deviation from the daily mean (Ruppert & Hohenegger, ; Schulz & Stevens, ). ω SW is shown in Figure d for night and day.…”
Section: Resultsmentioning
confidence: 99%
“…where s is dry static energy, and [ ] ′ denotes a deviation from the daily mean (Ruppert & Hohenegger, 2018;Schulz & Stevens, 2018). SW is shown in Figure 3d for night and day.…”
Section: Resultsmentioning
confidence: 99%
“…Although CSA is often considered within an idealized modeling framework, a few recent studies have focused on the relevance of CSA to observations of organized convection in the tropical atmosphere (e.g., Holloway et al, ; Schulz & Stevens, ; Tobin et al, ). Holloway et al () showed that the dry region is too dry compared to observations in a ∼1,500 × 1,500‐km domain but is more humid and closer to observations in long‐channel simulations (∼12,000 × 200 km).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…As shallow cumulus convection is not expected to trigger at the same time and place in a model and reality, a statistical approach is adopted here, in which the airborne observations are compared to their model counterpart for different LWP regimes. The analysis in 80 LWP space is similar to the studies in moisture space that first have been published by Schulz and Stevens (2018) for groundbased observations and by Naumann and Kiemle (2019) for airborne observations. In the LWP space it is possible to study microphysical cloud processes like the transition from non-precipitating to precipitating clouds.…”
mentioning
confidence: 62%